Trends in Antimicrobial Usage on Swiss Pig Farms from 2018 to 2021: Based on an Electronic Treatment Journal - Ramona Wissmann; Dolf Kümmerlen; Thomas Echtermann (MDPI AG, 2024)
(1) Background: The aim of this retrospective observational study was to observe the trends in antimicrobial usage (AMU) from 2018 to 2021 in Swiss pigs based on an electronic treatment journal used nationwide by farmers. Thus, for the first time, standardized, longitudinal comparisons of AMU between the years could be analyzed, as well as the influence of targeted interventions, on farms with higher consumption. (2) Methods: The data was evaluated by different indicators, such as the amount of active ingredient in kilograms, treatment days per farm (ATI) and treatment incidence (TI) based either on animal-defined daily doses (TIADD) or used daily doses (TIUDD). Calculations were performed across the following five age categories: suckling piglets, weaners, fattening pigs, and gestating and lactating sows, and the proportions of antimicrobial classes were evaluated for each age category. (3) Results: The highest amount of the active ingredient was administered to the group of fattening pigs, while the suckling piglets received the lowest amount of the active ingredient. In 2021, there was a significant decrease in active ingredient consumption per pig, but a significant increase in ATI, TIADD and TIUDD compared to 2018. The largest proportion of AMU was attributed to penicillins each year, followed by sulfonamides and tetracyclines. The "Highest Priority Critically Important Antimicrobials" represented a proportion of overall usage, declining from 5.2% in 2018 to 3.1% in 2021, while polypeptides were the most used class of critical antimicrobials. Interventions on high-usage farms showed that some farms decreased their AMU in the following year while others did not. (4) Conclusions: This study reveals a decrease in the overall usage measured in kilograms per pig of antimicrobials in Swiss pigs between 2019 and 2021 through the monitoring of AMU, but, at the same time, there was an increase in treatment days or incidence per farm. Critical antimicrobials can be reduced regardless of the indicator. The significance and quality of interventions should be investigated in future studies.